ISLAMIC INTELLECTUAL CONTRIBUTIONS TO SCIENCE: THE LEGACY OF AL-KHWARIZM, AL-BIRUNI, AND IBN AL-HAYTHAM - Syamzan Syukur; Rahmawati; Muhammad Arif; Ahmad Yani; Naeha Bil Bina Huzaymi (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
This article explores the contributions of three classical Muslim scholars—Al-Khawarizmi, Al-Biruni, and Ibn al-Haytham—as representations of Islamic intellectualism in the fields of science and technology. Using a historical and descriptive-analytical approach, the study traces the pivotal roles these figures played in laying the foundations of various modern scientific disciplines, including mathematics, astronomy, optics, and the scientific method. Al-Khawarizmi is recognized as the pioneer of algebra and algorithmic thinking; Al-Biruni as a forerunner of empirical research and intercultural religious studies; and Ibn al-Haytham as the founder of experimental methodology in optics. The findings demonstrate that all three exemplified a distinctively Islamic model of knowledge—one that harmonizes rational inquiry with spiritual consciousness. Their intellectual legacies affirm that scientific achievement in Islam is inseparable from ethical values and transcendent goals. This article advocates the revitalization of classical Islamic intellectualism within contemporary science education to cultivate a humanistic, Tawhid-based scientific paradigm. The study also critiques the persisting dichotomy between religious and scientific knowledge that continues to hinder the development of an integrated Islamic epistemology.